Estudo teórico QTAIM e DFT dos compostos de coordenação: efeito quelato, titanocenos e ligação química - Santos, Hugo Felix Lima dos (2012)
This work is a study of coordination compounds by quantum theory of atoms in molecules (QTAIM), based on the topological analysis of the electron density of molecular systems, both theoretically and experimentally obtained. The coordination chemistry topics which were studied are the chelate effect, bent titanocene and chemical bond in coordination complexes. The chelate effect was investigated according to topological and thermodynamic parameters. The exchange of monodentate ligands on polydentate ligands from same transition metal increases the stability of the complex both from entropy and enthalpy contributions. In some cases, the latter had a higher contribution to the stability of the complex in comparison with entropy. This enthalpic contribution is explained according to topological analysis of the M-ligand bonds where polidentate complex had higher values of electron density of bond critical point, Laplacian of electron density of bond critical point and delocalization index (number of shared electrons between two atoms). In the second chapter, was studied bent titanocenes with bulky cyclopentadienyl derivative π-ligand. The topological study showed the presence of secondary interactions between the atoms of π-ligands or between atoms of π-ligand and -ligand. It was found that, in the case of titanocenes with small difference in point group symmetry and with bulky ligands, there was an nearly linear relationship between stability and delocalization index involving the ring carbon atoms (Cp) and the titanium. However, the titanocene stability is not only related to the interaction between Ti and C atoms of Cp ring, but secondary interactions also play important role on the stability of voluminous titanocenes. The third chapter deals with the chemical bond in coordination compounds by means of QTAIM. The quantum theory of atoms in molecules so far classifies bonds and chemical interactions in two categories: closed shell interaction (ionic bond, hydrogen bond, van der Waals interaction, etc) and shared interaction (covalent bond). Based on topological parameters such as electron density, Laplacian of electron density, delocalization index, among others, was classified the chemical bond in coordination compounds as an intermediate between closed shell and shared interactions